Trace elements in soil, plant and grain of corn plants cultivated in Latosols after sixteen years with application of sewage sludge - Yada, Marcela Midori [UNESP]; Melo, Wanderley Jose de [UNESP]; Melo, Valeria Peruca de (Assoc Brasileira Engenharia Sanitaria Ambiental, 2020)
One of the biggest concerns about the application of sewage sludge to the soil is due to contamination by trace elements, their persistence in the environment and high toxicity. The objective of this work was to evaluate the contents of the elements As, Ba, Cd, Cr, Cu, Hg, Mo, Ni, Pb, Se, and Zn in the soil, the plants, and the grains of corn, when grown in two latosols, after sixteen years with annual application of sewage sludge doses. The experiment was conducted under field conditions in Jaboticabal, SP. The experimental design was randomized blocks with 4 treatments and 5 replications. Treatments were: T1 = 0 control (mineral fertilization, without applying LE), T2 = 5 t ha(-1) LE, T3 = 10 t ha(-1) LE, and T4 = 20 t ha(-1) LE (dry basis). Applying LE doses of 10 and 20 t ha(-1) increased the available content of Cu in LVef soil and available levels of Cu, Ni, Pb and Zn in LVd soil, without exceeding the limits established by Brazilian legislation (prevention values). The levels of elements As, Ba, Cd, Cr, Hg, Mo, and Pb in maize grains remained below the limits established for human consumption.
Keywords: heavy metals; biosolids; bioavailability; municipal waste; environmental pollution